Design and construction of helical antenna for weather satellite receiver - Saleh, Zakaria (2001)
This report presents the theory, design, simulation and construction of a helical antenna for reception of orbiting weather Satellite signal from National Oceanic Atmospheric Administration (NOAA). This satellite transmits circular polarised AM-FM modulated signal at 137.5 MHz. The design and construction of this helical antenna was done with the aid of a computer program written in Turbo Pascal version 6. A program to simulate the radiation pattern of the helical antenna was also written in Turbo Pascal version 6. The constructed helical Antenna was tested and is perfectly matched. The gain of 13.01 dB, bandwidth of 23.5 MHz and half-power beamwidth of 36 degrees are achieved.